Pemetaan pola permukiman masyarakat di Kecamatan Klungkung: analisa pola dan karakteristik permukiman - Kohdrata, Naniek; Utami, Ni Wayan Febriana; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018, 2018)
Mapping of Klungkung sub-district settlement pattern: analysis of settlement pattern and characteristic. The research on Klungkung subdistrict settlement pattern aims to see whether the pattern is following “traditional” residential pattern theory or else. The pattern of community settlements can be used as an indicator of social dynamics as well as social problems. Similarly, it can be an indication of development potential or just the opposite for a development, whether from economic, social, cultural, even political. This study is limited only to find early indications of settlement patterns and residential characteristics. The method used is descriptive qualitative by utilizing GIS software to map residential locations obtained from key respondents and public respondents. The results show that the distribution of growing settlements patterns from core towards outside is the characteristics of the population based on religion or belief. While the pattern of settlements based on the character of the profession/work shows an orbital form, like the planets that surround the sun. Ethnic or race character does not show any particular pattern. This research is a preliminary study on the pattern of settlements in the era of globalization and development of Semarapura city in Klungkung regency. There is a tendency that the settlement pattern is not centered oriented anymore.